XAFS studies and computational simulation of calixcrowns-caesium complexes in solution - Gao, Jian Xun (Journal of synchrotron radiation, 2005)
Caesium L(3)-edge XANES (X-ray absorption near-edge structure) and EXAFS (extended X-ray absorption fine structure) have been evaluated as means of probing the local structure and the interaction of caesium ions with BPC6 {1,3-alternate bis(2-propyloxy)calix[4]arenecrown-6}, BOC6 {1,3-alternate bis(octyloxy)calix[4]arenecrown-6} and BisC6 (1,3-alternate calix[4]arene bis-crown-6) in NPME (o-nitrophenyl methyl ether) or OA (n-octyl alcohol). The XANES results indicate that the molecular symmetry is enhanced as the caesium ions are embedded. The EXAFS spectra demonstrate that the coordination numbers (N) and average distances (R) from the central caesium ion to the O atoms are: for BPC6, N = 7.0, R = 3.22 Angstroms (in NPME), and N = 7.0, R = 3.23 Angstroms (in OA); for BOC6, N = 6.8, R = 3.28 Angstroms (in NPME), and N = 6.9, R = 3.27 Angstroms (in OA); for BisC6, N = 6.9, R = 3.21 Angstroms (in NPME). Density functional theory at the triple-zeta adding polarization basis set level was used to simulate the BPC6, BOC6 and BisC6 coordination with the caesium ions. Data show that the seven-oxygen-configuration average distances from the central caesium ion to the O atoms are R = 3.38 for BPC6, R = 3.40 for BisC6 and R = 3.39 for BOC6